The Strategic Importance of Energy Consumption to Economic Growth: Evidence from the UAE - Alshami, Mohamed A.; Sabah, Ariba (International Journal of Energy Economics and Policy, 2019)
Energy consumption is one of the strategic concerns for economies around the world, especially in view of depletion of natural resources which ultimately affects economic growth. Interestingly, policy makers in an oil-rich country such as the United Arab Emirates (UAE) have taken steps to bring about efficiency in energy consumption to accelerate the pace of economic growth. Therefore, the objective of the study was to test the relationship between economic growth and electricity consumption in the UAE. The data for the study related to the years between 1985 and 2017. The research used 4 variables including electricity consumption per capita, GDP in current US dollars, labor force and gross capital formation. The study employed unit root test, cointegration analysis and granger causality for making the analysis. We concluded that the variables had unit root at level and stationery at first difference. The bivariate cointegration test showed that electricity consumption had cointegration equation with capital gross fixed formation, GDP and labor force. Finally, the granger causality test showed one directional causality from GDP to electric power consumption and labor force to electric power consumption. Keywords: energy consumption, economic growth, correlation, UAE JEL Classifications: C33, O13, O38, Q43, O47 DOI: https://doi.org/10.32479/ijeep.8289